1992
DOI: 10.1073/pnas.89.21.10405
|View full text |Cite
|
Sign up to set email alerts
|

Copper,zinc superoxide dismutase is primarily a cytosolic protein in human cells.

Abstract: The intracellular lalization of human copper,zinc superoxide dismutase (Cu,Zn-SOD; superoxide:superoxide oxidoreductase, EC 1.15.1.1) was evaluated by using EM immunocytochemistry and both Isolated human cell lines and human tissues. Eight monoclonal antibodies raised against either native or recombinant human Cu,Zn-SOD and two polyclonal antibodies raised against either native or recombinant human Cu,Zn-SOD were used. Fixation with 2% paraformaldehyde/0.2% glutaraldehyde was found necessary to preserve normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
251
0
11

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(271 citation statements)
references
References 11 publications
9
251
0
11
Order By: Relevance
“…SOD-1 is a protective enzyme responsible for maintaining lower levels of superoxide radicals within the cell (Fridovich, 1978;Bannister et al, 1987;Crapo et al, 1992). Previous studies have shown that down-regulation of SOD-1 activity induces apoptosis of neuronal cells (Troy and Shelanski, 1994) and that up-regulation of SOD-1 by shear stress is an important mechanism preserving the integrity of the endothelium after pro-apoptotic stimulation (Dimmeler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…SOD-1 is a protective enzyme responsible for maintaining lower levels of superoxide radicals within the cell (Fridovich, 1978;Bannister et al, 1987;Crapo et al, 1992). Previous studies have shown that down-regulation of SOD-1 activity induces apoptosis of neuronal cells (Troy and Shelanski, 1994) and that up-regulation of SOD-1 by shear stress is an important mechanism preserving the integrity of the endothelium after pro-apoptotic stimulation (Dimmeler et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc, for example, can alter cellular signal transduction (1), DNA synthesis (2, 3), gene transcription (4,5), post transcriptional modifications (6), protein-protein interactions (7), and protein function (8,9). Increases or decreases in intracellular zinc have been associated with apoptotic cell death (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…CuZnSOD converts superoxide (O 2 À ) to H 2 O 2 (Fridovich, 1995) and is the major superoxide scavenger in the cytoplasm, nucleus, lysosomes, and intermembrane space of mitochondria (Chang et al, 1988;Keller et al, 1991;Crapo et al, 1992;Sturtz et al, 2001). CuZnSOD (SOD1, Sod1) transgenic and mutant mice have been widely used to study the role of oxygen free radicals in different experimental systems (Huang et al, 2002;Kruidenier et al, 2003).…”
Section: Introductionmentioning
confidence: 99%